Carbamylation of vimentin is inducible by smoking and represents an independent autoantigen in rheumatoid arthritis. Issue 7 (9th February 2017) - Ospelt, Caroline; Bang, Holger; Feist, Eugen; Camici, Giovanni; Keller, Stephan; Detert, Jacqueline; Krämer, Anette; Gay, Steffen; Ghannam, Khetam; Burmester, Gerd R
Abstract : Objectives: Smoking has been connected to citrullination of antigens and formation of anti-citrullinated peptide antibodies (ACPAs) in rheumatoid arthritis (RA). Since smoking can modify proteins by carbamylation (formation of homocitrulline), this study was conducted to investigate these effects on vimentin in animal models and RA. Methods: The efficiency of enzymatic carbamylation of vimentin was characterised. B-cell response was investigated after immunisation of rabbits with different vimentin isoforms. Effects of tobacco smoke exposure on carbamylation of vimentin and formation of autoantibodies were analysed in mice. The antibody responses against isoforms of vimentin were characterised with respect to disease duration and smoking status of patients with RA. Results: Enzymatic carbamylation of vimentin was efficiently achieved. Subsequent citrullination of vimentin was not disturbed by homocitrullination. Sera from rabbits immunised with carbamylated vimentin (carbVim), in addition to carbVim also recognised human IgG-Fc showing rheumatoid factor-like reactivity. Smoke-exposed mice contained detectable amounts of carbVim and developed a broad immune response against carbamylated antigens. Although the prevalence of anti-carbamylated antibodies in smokers and non-smokers was similar, the titres of carbamylated antibodies were significantly increased in sera of smoking compared with non-smoking RA. CarbVim antibodies were observed independently of ACPAs in early phases of disease and double-positive patients for anti-mutated citrullinated vimentin (MCV) and anti-carbVim antibodies showed an extended epitope recognition pattern towards MCV. Conclusions: Carbamylation of vimentin is inducible by cigarette smoke exposure. The polyclonal immune response against modified antigens in patients with RA is not exclusively citrulline-specific and carbamylation of antigens could be involved in the pathogenesis of disease. Trial registration number: ISRCTN36745608 ; EudraCT Number: 2006-003146-41.